Slaying the vampire conqueror - Broadbent, Carissa (Broadbent, Carissa. Crowns of Nyaxia novel., 2025)
"Sylina has sacrificed everything for her goddess--her soul, her freedom, her eyes. Life in service to the Arachessen, a cult of the Goddess of Fate, has turned Sylina from orphaned street-rat to disciplined killer, determined to overthrow Glaea's tyrannical king. Butwhen a brutal vampire conqueror arrives on their shores, Sylina faces an even deadlier adversary. She's tasked with a crucial mission: infiltrate his army, earn his trust--and kill him"--